(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Nonwoven geotextiles manufactured by mechanical carding process and bonding by needling process are investigated in this paper. Part of the samples was additionally bonded by thermal calendaring process. Sampling was conducted according to the standard for geotextile with certain modifications. The samples were tested for water permeability perpendicular to the plane of samples using loads of 2, 20 and 200 kPa. Characteristic opening size of geotextiles was tested using sieving method. Research shows that different applied pressures significantly change structure and properties i.e. thickness and water permeability normal to the plain under load of geotextile.